Impact of Social Media on Students Entrepreneurial Orientation: A Study of Selected Institutions in Nigeria - P. O., Adebayo (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2015)
Regardless of huge prospects for entrepreneurial opportunity exploitation as provided by online social media, students’ predispositions to opportunity identification and business startup have been low. This has resulted to poor innovation, less business startup intention, and ultimately increased graduate unemployment in most developing nations. This study attempts to investigate the impact of online social networking on students’ entrepreneurial orientation. A survey of 185 undergraduates across various disciplines was selected from five tertiary institutions through a self-administered questionnaire. The data were analysed using both descriptive and inferential statistical tools with the aid of SPSS 1 6.0. The result revealed active engagement of students in online social network sites such as WhatsApp, LinkedIn, Instagram, and Facebook among others. However, the test of hypothesis revealed an insignificant relationship between online social networks and students’ willingness to startup a business. The study recommends that students need to change their orientation towards embracing online social network as a platform for business idea generation, opportunity identification and business networking.